SISTEM INFORMASI PENGGAJIAN PEGAWAI PADA PERUSAHAAN PT. AGRO MUKO BUNGA TANJUNG POM - Erna Sari Agustina; Rijois Iboy Erwin Saragih; Eviyanti Novita Purba (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2021)
The employee payroll information system is a system built to simplify and save time so that employee payroll is precise and accurate. Salary is an income as a reward from the employer to the employee for a job or service that has been or is performed and is declared or valued in the form of money determined on the basis of an agreement or legislation and paid on the basis of a work agreement between the employer and the employee including allowances. , both for the employees themselves and for their families. The purpose of this research is to design a payroll system that uses a web-based system so that it can make it easier to manage data and make it easier to analyze reports. The results of the application can make it easier for the employee payroll system to be forwarded to implementation so that this system can be applied for company needs. With the employee payroll system that still uses the manual method, a web-based payroll system is made which is expected to overcome the problems contained in the report, speed up and save the time needed so that performance can be faster and maximal. Making payroll applications for employees of PT. Agro Muko Bunga Tanjung Pom used by the author is to use the programming language php and myql as a database to assist in the process of inputting employee payroll data.